The Effectiveness of Online Learning For Business Administration Students at Indragiri College - Safitri, Reza (Green Publisher Indonesia, 2022)
The Covid-19 outbreak has made everything change routine, including in terms of education. In the past, learning in universities was carried out face-to-face, but now learning must be carried out online. The purpose of this study was to find out how much effective online learning is during the covid 19 pandemic for Business Administration students at the STIA Indragiri college. This study uses a descriptive qualitative model. Respondents from this study amounted to 26 students. The results of this study indicate that students want face-to-face learning, while some students want online learning, so it can be concluded that continuous online learning during this pandemic is very ineffective.